Congenital Infections with Human Herpesvirus 6 - Ortwin Adams; C. Krempe; Gesine Kögler; Peter Wernet; Andreas Scheid (1998)
Cord blood DNA was tested for the presence of human herpesvirus 6 (HHV-6) DNA by the polymerase chain reaction. Specific DNA could be detected in the specimens of 5 (1.6%) of 305 babies born to ostensibly healthy mothers, indicating that intrauterine infection had occurred. These transmissions would not have been detected by serologic methods, because no specific IgM antibody could be found in the fetal sera. These results indicate that, in addition to infections acquired in early childhood, congenital infections may account for the HHV-6 seropositivity in children.